Monitoring system the internal corrosion of gas-line by means of digital signal processing - Junior, Carlos Antonio Berto (2008)
Natural gas has hazardous contaminants for its quality. For in such a way the present residual water condensation in the gas can start a local corrosive process, which could cause damage to the structure of the gas ducts. Due to the great length of a gas duct, corrosive components decrease its quality and cause great operational problems. Currently the techniques adopted for such evaluation consist of the inclusion of a body of test known as PIG, with sweepings by means of ultrasound and thermograph, beyond carried through special surveys of field on the surface of the ground. Both continuous monitoring of these ducts and the use of predictive maintenance methods are important to evaluate their wall thickness. The detection process may be optimized by monitoring their internal region with an independent element with infrared cameras. They supply images, which will be later processed and digitally recorded in a non-volatile memory. A specific software has been developed in order to verify their images, by identifying non-conformities and guide the maintenance process.